New Mexican and Central American species of Agrilus Curtis (Coleoptera: Buprestidae) mimetic of flies - Hespenheide, Henry A. (Zootaxa, 2012)
The genus Agrilus participates in a number of mimicry complexes. At least 23 species in México and Central America areconsidered to belong to one of the complexes that putatively have flies as models. In this complex, characterized by thecolor pattern of red-blue/black-pale, 11 new species are described —Agrilus updikei, new species; Agrilus marthae, newspecies; Agrilus dipterioides, new species; Agrilus opitzi, new species; Agrilus exquisitus, new species; Agrilus zumba-doi, new species; Agrilus coloradoensis, new species; Agrilus frankparkeri, new species; Agrilus cavei, new species;Agrilus alajuelensis, new species; and Agrilus percaroides, new species. Two species groups are recognized, based onAgrilus basalis Chevrolat and A. percarus Kerremans. Previously described species are provided with a diagnosis or redescribed, and additional specimen records are given. All species are illustrated.